2002
DOI: 10.1097/00005344-200205000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning Attenuates the Shortening of Recovery During Coronary Occlusion in Isolated Rabbit Hearts With d-Sotalol-Induced Long QT Intervals

Abstract: The effects of 20-min ligations of the anterior branch of the left coronary artery were studied in Langendorff-perfused rabbit hearts with 92 microM D-sotalol added to the perfusate to induce long QT intervals and triggered arrhythmias. Epicardial electrograms, a left ventricular endocardial monophasic action potential, and simulated X and Y lead electrocardiograms were used to characterize ventricular conduction and recovery. In contrast to previous work showing that global ischemia eliminated triggered activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…After sedation the rabbits were heparinized (500 U iv) and euthanized with propofol (100 mg iv). Our preparation was published previously (46). The hearts were removed via a midsternal thoracotomy and rinsed in cool, oxygenated Tyrode solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sedation the rabbits were heparinized (500 U iv) and euthanized with propofol (100 mg iv). Our preparation was published previously (46). The hearts were removed via a midsternal thoracotomy and rinsed in cool, oxygenated Tyrode solution.…”
Section: Methodsmentioning
confidence: 99%
“…Ten additional hearts underwent classic ischemic preconditioning (Precon). Hearts were preconditioned by two global ischemic episodes of 5 min in duration at a perfusion rate of 2.5 ml/min and separated by 10 min (46). Ten minutes after the second preconditioning episode, coronary occlusion was performed for 30 min, followed by 2 h of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…More recently Lu et al (44) showed phosphorylation of Tfam not only alters its DNA binding ability, but also its sensitivity to Lon mediated degradation (54) under conditions when catalytic subunit of PKAα was forcibly expressed in mitochondria. Studies from our laboratory showed that PKA mediated phosphorylation of CcO subunits I, IVi1 and Vb during pathophysiological conditions of hypoxia and myocardial ischemia/reperfusion renders them more sensitive to degradation (4, 810, 2628). In support, Hori et al showed that ER stress transmitted to mitochondria also induce degradation of CcO II, IVi1 and Vb in a Lon dependent manner (52).…”
Section: Discussionmentioning
confidence: 99%
“…Hearts from New Zealand male white rabbits (2–2.5 kg) were removed after euthanasia and perfused using a Langendorff perfusion apparatus as described before (4;28). The aorta was cannulated and the heart suspended on a Langendorff perfusion apparatus in which the coronary arteries were perfused from a reservoir with oxygenated temperature-controlled Tyrode’s solution at a constant pressure of 80 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally thought that IP is able to limit the mass of myocardium at risk that ultimately becomes infarcted and results in reducing lethal arrhythmia. 2,3 However, lack of IP enhanced inflammatory response, and subsequent left ventricle (LV) dysfunction, are related to VT/VF development after AMI. 4 It has also been reported that cardioprotection with IP is related to the enhanced expression of angiogenic growth factors, such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factors (bFGF) after MI.…”
mentioning
confidence: 99%